Routine laboratory biomarkers as prognostic indicators of cardiac sarcoidosis outcomes - Kolluri, Nikhil; Schmidt, Tyler; Elwazir, Mohamed; Kapa, Suraj; AbouEzzeddine, Omar; Bois, John; Schirger, John; Rosenbaum, Andrew; Cooper, Leslie (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Biomarkers to monitor disease activity and predict major adverse cardiac events (MACE) in CS have not been described previously. We aimed to identify biomarkers to predict MACE in cardiac sarcoidosis (CS). Methods: Patients (N=232) diagnosed with CS were retrospectively enrolled. Biomarkers including angiotensin-converting enzyme (ACE), N-terminal brain natriuretic peptide (NT-proBNP), troponin T, and creatinine levels were evaluated against a primary end point of left ventricular assist device implantation, heart transplantation, or death, and a secondary end point of cardiac hospitalization-free survival. Results: Troponin T (hazard ratio [HR], 1.06 per 0.01 ng/mL; P=.006), NT-proBNP (HR, 1.31 per 1,000 pg/mL; P<.001), and creatinine (HR, 4.02 per mg/dL; P=.01) were associated with the primary end point, even after adjusting for ejection fraction. NT-proBNP, B-type natriuretic peptide (BNP), creatinine, albumin, and calcium were associated with the secondary end point (P<.05). ACE levels were associated with presence of late gadolinium enhancement (LGE) on cardiac magnetic resonance (CMR) imaging (mean difference, 14.7; P=.03); 1,25 dihydroxyvitamin D (1,25-OHVit-D) was associated with uptake on cardiac 18F-flurodeoxyglucose position emission tomography (FDG-PET, P=.03). Conclusions: Troponin T, NT-proBNP, and creatinine predict clinically significant outcomes in CS. ACE levels correlated with LGE on CMR, and 1,25-OHVit-D levels correlated with FDG-PET activity.